PENGARUH KEPUASAN KERJA, KOMITMEN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA FASILITATOR PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PEDESAAN DI KABUPATEN INDRAGIRI HILIR - Hakim, Abdul; Oemar, Yohanas; Marnis, Marnis (Jurnal Tepak Manajemen Bisnis, 2016)
This study aims to determine the effect of variable job satisfaction, commitment to work, and working environment on the performance of the facilitator PNPM Rural in Indragiri Hilir. This research was conducted on the facilitator PNPM Rural in Indragiri Hilir of 60 people. In testing the hypothesis menggunaka statistical analysis using multiple linear regression analysis using SPSS analysis tools.The results showed that the variable is independent (job satisfaction and job commitment) had no significant effect on the performance of the facilitator. Only variable working environment has a significant influence on the performance of the facilitator PNPM Rural in Indragiri Hilir.The theoretical implications that can be derived from this research is the result of this study showed that facilitators work directly related to masyaraat the placement factor and maintain the condition of the surrounding community became noteworthy. Downstream conditions of the district are relatively safe indragiri be one contributing factor comfort in the work of facilitators. To produce optimal performance, it is recommended should the facilitator PNPM Rural in Indragiri Hilir equipped with good communication skills so that they can be accepted by all elements of society who become surrogate .